Acquired hemophilia in patient with Systemic lupus erythematosus: Clinical case report - S. A. Alekseeva; N. I. Zozulya; T. M. Reshetnyak (Научно-практическая ревматология)
Acquired hemophilia is a rare disease that develops because of the synthesis of antibodies to endogenous VIII blood clotting factor. The most common symptom of acquired hemophilia is spontaneous bleeding. Acquired hemophilia is observed more frequently in older population and in 50% is secondary to malignant tumors and autoimmune rheumatic diseases. In this article, we present a clinical case of autoimmune hemophilia that developed shortly before the onset of systemic lupus erythematosus.